Perbaikan Kualitas pada Proses Kiln Tegel Keramik Kode GE dengan Metode Six Sigma DMAIC (Studi Kasus PT. IKAD Tangerang) - Eko Liquiddanu; Retno Wulan Damayanti; Febiyanto S (Performa: Media Ilmiah Teknik Industri, 2007)
PT. IKAD is a company that produces ceramic tile. Quality decreasing is occurred on some Critical To Quality (CTQ) in a part of kiln. Kiln process itself was the last process and the most vital in determining final output of ceramic tile. Realizing the importance to the quality of kiln process, hence needed a problem solving method to improve and control process which taking place in Department Plant 3 so the amount ofdefect product can be minimized to achieve zero defect. The method to solve the problem is Six Sigma method that consist of Define, Measure, Analyze, Improve, and Control (DMAIC) phase. DMAIC phase begins with identifying customer needs to determine priority ofCTQ. Then measuring the sigma level, stability and process capability ofpriority CTQ. On the analyze phase, cause effect diagram is used to find failure cause analysis of CTQ, and then Failure Modes Effect Analysis (FMEA) tool is used to analyze the failure. On the final phase, improvement plan and process control act is done for company. The result ofthis research from Define phase is dash away as the priority ofCTQ. On the Measure phase known that sigma level in the month of January 2006 equal to 3,46 sigma and decrease to 3,24 sigma in Februari 2006. At that both period, process condition is not stable but capable enough if seen from Cp and Cpk value. On the Analyze phase is obtained the information that many factors like process or method, man, material, measurement, mother-nature, also machine and equipments are supposed causing instability and incapability of kiln process. Improve suggestions for managerial and technical side are given and Control suggestions to guarantee the quality of kiln process are also given on the Improve and Control phase.